Fundamental determinants of exchange rate expectations - Joscha Beckmann; Robert L. Czudaj (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2022)
This paper provides a new perspective on the exchange rate disconnect puzzle by referring to the expectations building mechanism in foreign exchange markets. We analyze the role of expectations regarding macroeconomic fundamentals for expected exchange rate changes. In doing so, we assess real-time survey data for 29 economies from 2002 to 2020 and consider expectations regarding GDP growth, inflation, interest rates, and current accounts. Our empirical findings show that fundamentals expectations are more important over the long run compared to the short run. We find that an expected increase in GDP growth relative to the US leads to an expected appreciation of the domestic currency while higher relative inflation expectations lead to an expected depreciation, a finding consistent with purchasing power parity. Our results also indicate that the expectation building process differs systematically across pessimistic and optimistic forecasts with the former paying more attention to expected fundamentals. Finally, we also observe that incorporating expected fundamentals tends to reduce forecast errors over the long run.
Keywords: F31; F37; G17; 330; Exchange rates; Expectations; Forecast errors; Fundamentals; Survey data